Samorządność a przynależność polityczna - Kolczyński, Mariusz; Faracik-Nowak, Magdalena (Political Preferences, 2013)
The main aim of this article is to identify current issues in the field of local government in Poland, especially the local political elites in the context of their political affiliation. The decentralization process and the gradual transfer of the responsibilities of the national regional and local dimension has led to the development of self-government. This in turn enabled the participation in the process of governance every citizen of the inhabited area. Recent local elections show that localism is a relative term and greatly simplified. Each of the local politician has own connections with a specific option. Those behavior leads to a kind of self-governance crisis that manifests itself among other things: a decrease of public trust, low voter turnout and increase the sense of social alienation.